Birooted primary canines identified in 8-year-old Japanese girl – Case report. Issue 1 (April 2019) - Kokomoto, Kazuma; Okawa, Rena; Naka, Shuhei; Nomura, Ryota; Nakano, Kazuhiko
Abstract: This report presents a rare case of birooted bilateral maxillary primary canines. A Japanese girl aged 8 years 10 months was referred to the Pediatric Dentistry Clinic of Osaka University Dental Hospital by an orthodontic dentist to extract maxillary bilateral primary canines. The canines appeared to be birooted in panoramic radiography and were extracted under infiltration anesthesia. Both visual observation and computed tomography findings revealed that the birooted primary canine had 2 roots for each root canal. In spite of the rareness of this condition, it should be kept in mind because of potential problems in affected patients.